(untitled) (mathematica didactica, 2003)
Different studies show rigid beliefs of teacher students concerning mathematics and teaching mathematics. These beliefs can hardly be changed. However this is a special task of teacher’s education, if perspectives of mathematics instruction for the future are to be developed. Studies and experiences of my own with teacher students for primary and first secondary schools show steps to a development, particularly from which expectations of students can be started.